Model of real estate life cycle cost control - Nikolaieva, T. (Ways to Improve Construction Efficiency, 2015)
Based on the concept of life cycle, the necessity of real estate full costs of preparation, construction and operation accounting on the entity level, monitoring and on this basis the use of state property by the authorized governance bodies is justified. The model of centers of cost formation and adjustment of major proportions between them in order to extend the period of operation and reduce the cost of the facilities life cycle is proposed.